Respon Pertumbuhan dan Hasil Tanaman Timun Apel (Cucumis sp.) Akibat Pemberian Jenis Media Tanam dan NPK Majemuk 15:15:15 - Fauzi, Wildan; Saputro, Nurcahyo Widyodaru; Agustini, Rika Yayu (JURNAL AGROPLASMA, 2024)
The use of planting media is husk charcoal, sawdust and Cocopeat derived from agricultural waste. Husk charcoal, sawdust and Cocopeat can increase nutrient absorption for plants which can be combined with 15:15:15 compound NPK fertilizer, so that it can help increase the growth and yield of Apple Cucumber (Cucumis sp.) plants. The objective of this study was to identify the optimal combination of planting media types and NPK compound 15:15:15 for the growth and yield of apple cucumber plants. The research was conducted in Pasirjengkol Village, Majalaya District, Karawang Regency 41371 from March 2023 to May 2024. The method used was a single-factor Group Randomized Design (RAK) with 10 treatments, 3 replicates and 2 plant samples. This resulted in 60 experimental units, consisting of: A (Control soil + NPK 300 kg/ha), B (Soil + husk charcoal (1:1) + NPK 200 kg/ha), C (Soil + sawdust (1:1) + NPK 200 kg/ha), D (Soil + Cocopeat (1:1 The following treatments were applied: A (control soil + NPK 300 kg/ha), B (soil + husk charcoal (1:1) + NPK 200 kg/ha), C (soil + sawdust (1:1) + NPK 200 kg/ha), D (soil + Cocopeat (1:1 The following treatments were applied: 00 kg/ha, H (Soil + husk charcoal (1:3) + NPK 400 kg/ha), I (Soil + sawdust (1:3) + NPK 400 kg/ha), J (Soil + Cocopeat (1:3) + NPK 400 kg/ha). The results of the experiment will be subjected to the F test to ascertain the veracity of the observed effect. Should the effect be deemed genuine, it will be subjected to further testing using the Duncan Multiple Range Test (DMRT) at the 5% level. The results demonstrated that the treatment of planting media types and NPK compound 15:15:15 Bern has a tangible impact on plant growth and yield. The treatment J (soil + Cocopeat (1:3) + NPK 400 kg/ha) yielded the most favorable results for tendril length (132.667 cm), stem diameter (4.367 mm), number of leaves (56 strands), and fruit weight (338.833 grams). Keywords: apple cucumber, husk charcoal, sawdust, cocopeat, NPK